A Practical Hand Book for Biotechnology, Microbiology & Biochemistry - Dr. S.M Fazeela Mahaboob Begum; Dr. Venkatalakshmi Ranganathan; B. Harshitha; V. Ashwini; R. Anushri (A Practical Hand Book for Biotechnology, Microbiology & Biochemistry, Edition 1, 2024)
This handbook serves as a comprehensive guide for students, researchers, and professionals in the fields of biotechnology, biochemistry, and microbiology. Designed as a practical resource, it bridges the gap between theoretical knowledge and laboratory skills, offering detailed protocols and best practices for conducting experiments in these interconnected disciplines. The book is divided into three main sections, each focusing on core areas of biotechnology, biochemistry, and microbiology. It includes step-by-step methodologies for essential techniques such as nucleic acid isolation, protein purification, enzymatic assays, pharmacology analysis, microbial culture, and biochemical analysis. Each chapter begins with an introduction to the underlying scientific principles, followed by clear, concise instructions and troubleshooting tips to ensure successful experimental outcomes. In addition to experimental protocols, the handbook provides insights into principles, applications, and high-throughput screening techniques, emphasizing their relevance in academic and industrial research. Safety guidelines, reagent preparation, and data analysis strategies are also covered to equip readers with a well-rounded understanding of laboratory practices.